Factors Influencing the Performance of Small and Micro Enterprises (Smes) in Somaliland a Case Study of Hargeisa City (Global Journal of Management and Business Research, 2017)
Governments worldwide have acknowledged the impact of Micro and Small Enterprises (MSEs) on job creation, improvement of people's standards of living and hence an overall impact on the economy. The important role played by the informal sector in most economies in less developed countries is now recognized by governments and international agencies. However, enterprises in the informal sector continue to encounter various barriers that prevent them from attaining their full potential. This study sought to establish the factors that influence the performance of MSEs inhargeisa city.
Keywords: Legislative processes: acquisition of permits; tax procedures